Prevalence of human papillomavirus in teenage heterosexual males following the implementation of female and male school-based vaccination in Australia: 2014–2017. Issue 46 (31st October 2019) - Chow, Eric P.F.; Tabrizi, Sepehr N.; Fairley, Christopher K.; Wigan, Rebecca; Machalek, Dorothy A.; Regan, David G.; Hocking, Jane S.; Garland, Suzanne M.; Cornall, Alyssa M.; Atchison, Steph; Bradshaw, Catriona S.; McNulty, Anna; et al.
Abstract: Background: Australia introduced a school-based human papillomavirus (HPV) vaccination program for females aged 12–13 years in 2007, with a three-year catch-up to age 26; and for boys aged 12–13 from 2013, with a two-year catch-up to age 15. This study aimed to compare the prevalence of penile HPV between teenage heterosexual males in cohorts eligible or non-eligible for the school-based male vaccination program. Methods: Between 2014 and 2017, sexually active heterosexual males aged 17–19 were recruited from sexual health centres and community sources across Australia. Males provided a self-collected penile swab for 37 HPV genotypes using Roche Linear Array and completed a questionnaire. We calculated adjusted prevalence ratios (aPR) of HPV between males in two periods: 2014–2015 (preceding implementation of school-based male vaccination) and 2016–2017 (eligible for school-based male vaccination). Self-reported vaccine doses were confirmed with doses reported to the National HPV Vaccination Program Register. Results: Overall, 152 males were recruited in 2014–2015 and 146 in 2016–2017. Numbers of female sex partners and condom use did not differ between the two periods. The prevalence of quadrivalent vaccine-preventable [4vHPV] genotypes (6/11/16/18) was low in both periods (2.6% [2014–15] versus 0.7% [2016–17]; p  = 0.371; aPR 0.28 [95% CI: 0.03–2.62]). Compared with men in 2014–2015, men in 2016–2017 had a lower prevalence of any of the 37 HPV genotypes tested (21.7% versus 11.6%; aPR 0.62 [95% CI: 0.36–1.07]) and any of the 13 high-risk genotypes tested (15.8% versus 7.5%; aPR 0.59 [95% CI: 0.30–1.19]). Prevalence of low-risk HPV genotypes did not differ between the two periods. Of the males recruited in 2016–2017, 55% had received ≥1 vaccine dose. Conclusion: The prevalence of 4vHPV genotypes among teenage heterosexual males in both cohorts was low, presumably due to herd protection from the female-only vaccination program. Further studies are required to determine the impact of universal HPV vaccination on HPV prevalence in males.